Gene S-phase kinase associated protein 2 is a novel prognostic marker in human neoplasms - Guo-Sheng Li; Tao Huang; Hua-Fu Zhou (BMC, 2023)
Abstract Background Neoplasms are a series of diseases affecting human health. Prognostic and tumor status-related markers for various tumors should be identified. Methods Based on 19,515 samples from multiple sources, for the first time, this study provided an overview of gene S-phase kinase associated protein 2 (SKP2) in pan-cancer. Differential SKP2 expression in multiple comparison groups was identified by the Kruskal-Wallis test and Wilcoxon rank-sum test. The prognosis significance of SKP2 in individuals with neoplasm was evaluated through univariate Cox regression analysis and Kaplan-Meier curves. The area under the curve was utilized to detect the accuracy of SKP2 in predicting cancer status. Spearman's rank correlation coefficients were calculated in all correlation analyses. Gene set enrichment analysis was used to identify essential signaling pathways of SKP2 in human neoplasms. Results The study disclosed the upregulated SKP2 expression in 15 neoplasms and decreased SKP2 expression in three cancers (p < 0.05). The transcription factor Forkhead Box M1 may contribute to the increased expression levels of SKP2 in certain tumors. Over-expressed SKP2 represented a risk factor for the prognosis of most cancer patients (hazard ratio > 1, p < 0.05). SKP2 expression made it feasible to distinguish neoplasm and control tissues of 21 neoplasms (sensitivity = 0.79, specificity = 0.87, area under the curve = 0.90), implying its potential in screening a series of neoplasms. Further, the research revealed the close association of SKP2 expression with DNA methyltransferases, mismatch repair genes, microsatellite instability, tumor mutational burden, neoantigen count, and immunity. Conclusions SKP2 plays an essential role in multiple neoplasms and may serve as a marker for treating and identifying these neoplasms.